If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -20 = 63 Reorder the terms: -20 + 18x = 63 Solving -20 + 18x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 18x = 63 + 20 Combine like terms: -20 + 20 = 0 0 + 18x = 63 + 20 18x = 63 + 20 Combine like terms: 63 + 20 = 83 18x = 83 Divide each side by '18'. x = 4.611111111 Simplifying x = 4.611111111
| 8(1+2x)=35 | | 1/5x-14 | | 24a-22=24a-4 | | 3y+22=180 | | -5(3-3x)+5x=-5x-15 | | ln(x)=21.72 | | 5w-2w=17 | | (3x+6)(-10x-10)= | | 12x+7=3x+16 | | -1=(-5x)^(-1/3) | | 4y=180 | | 217-t=365 | | 19=3(x-1)-(x-6) | | -10y-4y-8=-20 | | 1.2(x+3)= | | y=-16x^2+6x+200 | | 1/6x+2/3=1/4x-1/3 | | -1=(-5x)(-1/3) | | 29+x-5=180 | | 19+q=60 | | 4/x=12/27 | | 6x-64=2x-50 | | 5y+7=180 | | 4x^2/3-11x^1/3-3=0 | | 4x-6=3+(2x-4) | | 3m-7=11m+1 | | x+30=8x+44 | | 1-6p-3=16 | | 5w+10=3w+10 | | 10(12-3n)=-12(5n+5) | | 28+8n=4(4n-7) | | 1x=3y-7 |